2019
DOI: 10.1016/j.bbrep.2019.100663
|View full text |Cite
|
Sign up to set email alerts
|

Screening and selection of bacteria inhibiting white spot syndrome virus infection to Litopenaeus vannamei

Abstract: A total of 173 bacterial strains were isolated from different sources at different regions such as fermented foods, shrimp guts, sea water, mangrove water, and sediments. These bacteria were screened against white spot syndrome virus (WSSV) infection in Palaemon paucidens . Based on mortality, white spot level, and healthiness, three bacterial strains were selected and identified using 16S rRNA gene sequencing. These bacterial strains were Bacillus subtilis KA1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…WSSV isolates tested in bioassays generally induce the following clinical signs in infected white shrimp; lethargy, decreased food intake, discoloration of the hepatopancreas, cuticular loosening and red uropods [12]. Apart from these general clinical signs Shrimp infected with the CIAD isolate in the challenge bioassay showed 19% survival at 10 days post infection similar to the percentage obtained by Sekar, with 100% mortality until day 20 [34]. In contrast the, isolates from Angostura and Sonora induced 100% mortality between 3-and 10-days post-infection [35,2].…”
Section: Discussionsupporting
confidence: 53%
“…WSSV isolates tested in bioassays generally induce the following clinical signs in infected white shrimp; lethargy, decreased food intake, discoloration of the hepatopancreas, cuticular loosening and red uropods [12]. Apart from these general clinical signs Shrimp infected with the CIAD isolate in the challenge bioassay showed 19% survival at 10 days post infection similar to the percentage obtained by Sekar, with 100% mortality until day 20 [34]. In contrast the, isolates from Angostura and Sonora induced 100% mortality between 3-and 10-days post-infection [35,2].…”
Section: Discussionsupporting
confidence: 53%
“…Zebrafish infected with it had 100% death, but zebrafish treated with B. licheniformis experienced total survival after 30 days ( Girija et al, 2018 ). Also, in combination with B. Breve , an in vitro study showed significant inhibition against the adhesion of the pathogenic K. rhizophila ( Rohith and Halami, 2021 ) and anti-vibrio activity ( Sekar et al, 2019 ). The crude extract reveals antiviral activities against porcine epidemic diarrhea virus in Vero cells, and lower the viral shedding in piglets ( Peng et al, 2019 ), Also in piglets, the sodium butyrate generated by B. licheniformis improves Salmonella shedding ( Barba-Vidal et al, 2017 ).…”
Section: Clinical Trials Of Bacillus Licheniformismentioning
confidence: 99%
“…Due to the antagonistic activity of this probiotic, the complete survival of infected fish was observed in contrast with untreated fish [ 20 ]. This probiotic, in combination with Bifidobacterium breve , significantly inhibited the adhesion of the pathogen Kocuria rhizophila in vitro [ 21 ] and showed antivibrio activity against Vibrio parahaemolyticus [ 22 ]. The use of a crude extract from B. licheniformis resulted in marked antiviral activity against porcine epidemic diarrhea virus in Vero cells and reduced virus shedding in piglets [ 23 ].…”
Section: Introductionmentioning
confidence: 99%